ANALYZING THE DEGREE OF FREEDOM IN DECISION-MAKING IN THE MCDONALD’S FRANCHISE MODEL: THE PERSPECTIVE OF THE FRANCHISEE - SEVA-LARROSA, PEDRO; MARCO-LAJARA, BARTOLOMÉ; MARTÍNEZ-FALCÓ, JAVIER; RUIZ-FERNÁNDEZ, LORENA (Innovare Journal of Social Sciences, 2021)
Objective: The main objective of this study is to analyze the degree of freedom that the franchisee has in making business decisions compared to the corporate unit or, in other words, the degree of freedom that the franchiser grants the franchised establishment in managing its business. Methods: Franchising is one of the most widely used strategic alliances worldwide, mainly in two sectors: Retail and hospitality. This research is contextualized in the fast food industry, specifically in the McDonald’s restaurant chain. In order to reache the objective, five in-depth interviews have been carried out with franchisees of the well-known American company located in Spain. Results: The main findings show highly relevant information about the degree of freedom in the decision-making of McDonald’s franchisees which is scarce and limited since the decisions about the company are made and executed mostly by the franchiser. While the franchisees have a certain autonomy to hire their employees (human resources) and determine the marketing strategies (marketing), the supplies are managed and controlled by the franchiser. Conclusions: With regards to the results we can conclude that the corporate strategies are formulated and implemented by the franchiser itself due to its strategic nature. The competitive strategies are also the responsibility of the franchiser in the main, as he is in charge of building a certain competitive position. Nevertheless, it is the franchisees, encouraged by the franchisers, who incorporate technologies to their establishments to provide a better service. Finally, the functional strategies are those in which the franchisee has a greater degree of freedom. They focus on how to use and apply the resources and skills within each functional area.